CP-165 Impact on hospital readmission of medication reconciliation in post emergency geriatric unit: a pilot study. (25th February 2017) - Correard, F; Tabele, C; Daumas, A; Nail, V; Gayet, S; Gobin, N; Pellerey, M; Bertault-Peres, P; Villani, P; Honore, S
Abstract : Background: Medication reconciliation is a process used to identify and prevent medication errors at care transition points in hospitals. Medication errors are one of the more important factors those increase fatal injuries to patients and burden healthcare systems with significant economic costs. An appropriate medical history could reduce errors related to omission of drugs previously prescribed at the time of hospitalisation. In the current literature, the rate of hospital readmissions due to this type of error in older adults (>65 years old) is 14%. 1 Purpose: The objective of this study was to evaluate the 30 day readmissions in older adults as well as medication errors at the time of hospital admission and discharge. Material and methods: A monocentric prospective study was conducted in a post emergency geriatric unit to analyse medication reconciliation activity over a 5 month period. Each patient was called back 30 days after their exit from hospital. We compared medications prescribed at admission and at discharge with hospital physician prescription. Results: 110 patients were included in the study. At hospital admission, 52 medications errors (ME) were identified and 31 patients had more than 1 ME. Physicians accepted 46 pharmaceutical interventions (88%). The most frequent ME was omission of drugs (60%: amiodarone, ciclosporin, fluindione, pregabalin, digoxin and flecainide) followed by wrong dose (31%) and frequency (9%). At discharge, 81 medication reconciliations were performed and 33 ME were detected. Three types of discrepancies were noted: omission of drug (75%), wrong frequency (12%), wrong dose (6%) and other (7%). Over the 5 month period, 9% of patients were readmitted to hospital and 4% died. Conclusion: Our findings confirm that admission and discharge to hospital is a critical point for patient safety because ME occur at this time in almost half of elderly patients. We showed that the rate of hospital readmissions was less than reported in the literature. An interventional monocentric and randomised clinical trial (ConcReHosp) was recently started in our hospital to demonstrated the impact of medication reconciliation on early hospital readmission. References and/or acknowledgements: 1. HAS: Décision No2013.0050/DC/SMACDAM. Avril 2013. No conflict of interest